2023
DOI: 10.1002/ijgo.14809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID‐19 vaccinations on menstrual cycle and postmenopausal bleeding among health care workers: A cross‐sectional study

Abstract: Objective To determine the effect of coronavirus disease 2019 (COVID‐19) vaccination and its association with sociodemographic factors on the menstrual cycle in premenopausal women and on postmenopausal bleeding. Methods This is a retrospective cross‐sectional study conducted between September 22, 2022, and November 30, 2022, via a questionnaire distributed to 359 health care workers (HCWs) at Lebanese American University Medical Center–Rizk Hospital and St John's Hospital. Inclusion criteria included female L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Two studies did not find an association between hormonal contraceptives and menstrual abnormalities (Muhaidat et al, 2022;Duijster et al, 2023). Other significant associated factors that increased the risk were age (Lee et al, 2022;Morsi et al, 2022;Farah et al, 2023), greater body mass index (Farland et al, 2022), number of children (Muhaidat et al, 2022), marital status (Morsi et al, 2022;Muhaidat et al, 2022), smoking (Alvergne et al, 2023b), education level (Farah et al, 2023), being Hispanic of Latinx (Lee et al, 2022), and high selfreported perceived stress levels (Farland et al, 2022;Bisgaard Jensen et al, 2023). A history of COVID-19 infection decreased the risk in the study by Farland et al (OR = 0.58; 95%CI 0.32-1.04) (Farland et al, 2022), while Alvergne et al and Bisgaard Jensen et al found higher risks for this subgroup (PR = 1.46, 95%CI 1.22-1.75, OR = 2.17, 95%CI 1.40-3.35, respectively) (Alvergne et al, 2023b;Bisgaard Jensen et al, 2023).…”
Section: Covid-19 Vaccines and Menstrual Disordersmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies did not find an association between hormonal contraceptives and menstrual abnormalities (Muhaidat et al, 2022;Duijster et al, 2023). Other significant associated factors that increased the risk were age (Lee et al, 2022;Morsi et al, 2022;Farah et al, 2023), greater body mass index (Farland et al, 2022), number of children (Muhaidat et al, 2022), marital status (Morsi et al, 2022;Muhaidat et al, 2022), smoking (Alvergne et al, 2023b), education level (Farah et al, 2023), being Hispanic of Latinx (Lee et al, 2022), and high selfreported perceived stress levels (Farland et al, 2022;Bisgaard Jensen et al, 2023). A history of COVID-19 infection decreased the risk in the study by Farland et al (OR = 0.58; 95%CI 0.32-1.04) (Farland et al, 2022), while Alvergne et al and Bisgaard Jensen et al found higher risks for this subgroup (PR = 1.46, 95%CI 1.22-1.75, OR = 2.17, 95%CI 1.40-3.35, respectively) (Alvergne et al, 2023b;Bisgaard Jensen et al, 2023).…”
Section: Covid-19 Vaccines and Menstrual Disordersmentioning
confidence: 98%
“…Trogstad et al found a RR of 1.09 (95%CI 1.01-1.17) after the first dose, and a RR of 1.49 (95%CI 1.37-1.62) after the second dose (Trogstad et al, 2023). Other studies reported 1% (Farah et al, 2023), 2.4% (Taşkaldıran et al, 2022), 16% (Zhang et al, 2022), and19% (Duijster et al, 2023) of women experiencing intermenstrual bleeding after vaccination. (Caspersen et al, 2023).…”
Section: Covid-19 Vaccination and Breakthrough Bleedingmentioning
confidence: 98%
See 1 more Smart Citation